2013
DOI: 10.1152/jn.01000.2012
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity patterns of medial and lateral macaque frontal eye fields reveal distinct visuomotor networks

Abstract: It has been previously shown that small- and large-amplitude saccades have different functions during vision in natural environments. Large saccades are associated with reaching movements toward objects, whereas small saccades facilitate the identification of more detailed object features necessary for successful grasping and manual manipulation. To determine whether these represent dichotomous processing streams, we used resting-state functional MRI to examine the functional connectivity patterns of the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 99 publications
(99 reference statements)
1
24
0
Order By: Relevance
“…Some authors have argued for further subdivisions within these frontal oculomotor areas particularly within the FEF, which might reflect differentiable involvement in sensorimotor versus cognitive control demands during eye movement behavior (McDowell et al, 2008). This dissociation is well in line with reports of differential anatomical and functional connectivity of subregions within the FEF especially with the visual and parietal cortices as revealed by tracer and functional connectivity analyses in non-human primates (Babapoor-Farrokhran et al, 2013; Schall et al, 1995; Stanton et al, 1995). While potential homologues of (at least) the FEF and SEF have been described in the human brain using imaging techniques, localization varies between different studies making precise anatomical delineations rather difficult.…”
Section: Introductionsupporting
confidence: 91%
“…Some authors have argued for further subdivisions within these frontal oculomotor areas particularly within the FEF, which might reflect differentiable involvement in sensorimotor versus cognitive control demands during eye movement behavior (McDowell et al, 2008). This dissociation is well in line with reports of differential anatomical and functional connectivity of subregions within the FEF especially with the visual and parietal cortices as revealed by tracer and functional connectivity analyses in non-human primates (Babapoor-Farrokhran et al, 2013; Schall et al, 1995; Stanton et al, 1995). While potential homologues of (at least) the FEF and SEF have been described in the human brain using imaging techniques, localization varies between different studies making precise anatomical delineations rather difficult.…”
Section: Introductionsupporting
confidence: 91%
“…This is corroborated by anterograde and retrograde tracer studies, which show different patterns of connectivity for the two distinct neuronal populations: small-saccade neurons present more widespread projections to posterior (visual) regions of the brain while large-saccade neuron connectivity is more restricted (Stanton et al, 1995). This is confirmed by an fMRI study of spontaneous inter-regional activity co-variation of signal (resting-state functional connectivity) in five macaque monkeys that showed that the small-saccade FEF exhibits a stronger relation with visual ventral stream regions associated with object processing (Babapoor-Farrokhran et al, 2013). …”
Section: Discussionmentioning
confidence: 61%
“…Curiously, a different map has been reported in humans (Kastner et al 2007). This map of saccade amplitude in macaques corresponds to the variation in connectivity observed between areas 8l and 8m (Schall et al 1995, Babapoor-Farrokhran et al 2013. Saccade amplitude at the boundary between areas 8l and 8m is ∼15 • , which neatly partitions the FEF segment responsible for scrutinizing vision (8l) from that responsible for exploratory vision (8m).…”
Section: Generation Of Eye Movementsmentioning
confidence: 85%